Exposure to reversine affects the chondrocyte morphology and phenotype in vitro. (1st November 2017) - Gasparini, S.; Villa, F.; Molfetta, L.; Repaci, E.; Castagnola, P.; Quarto, R.; Giannoni, P.
Abstract: Articular chondrocytes derived from osteoarthritic tissues (OA HAC) show a severely reduced chondrogenic commitment. This impairment undermines their use for tissue‐engineered cartilage repair, which relies on cell proliferation and growth to meet therapeutic needs, but also on efficient cell plasticity to recover the chondrogenic phenotype. Reversine (Rev), a 2, 6‐disubstituted purine inhibitor of spindle‐assembly checkpoints, was described to convert differentiated mesenchymal cells to their undifferentiated precursors. We hypothesized that Rev exposure could divert OA HAC to more plastic cells, re‐boosting their subsequent commitment. HAC were enzymatically released from OA cartilage specimens, expanded for 2 weeks and treated with 5 μm Rev in dimethylsulphoxide (DMSO) or with DMSO alone for 6 days. Cell growth was assessed using the AlamarBlue TM assay. Cytoskeletal structure, endoproliferation and caspase‐3‐immunopositivity were assayed by epifluorescence microscopy. The OA HAC chondrogenic performance was evaluated by quantitative reverse transcription‐polymerase chain reaction (RT‐PCR) for glyceraldehyde‐3‐phosphate dehydrogenase, Sox9, Aggrecan (Agg), type II collagen (Col2), Ki67, cyclinD1, transforming growth factor‐β1 (TGF‐β1), ‐2 and ‐3, interleukin‐1β (IL‐1β) and ‐6, SMAD3 and ‐7, and vascular endothelial growth factor. Rev‐treated OA HAC recovered polygonal morphology and reduced Ki67 expression and proliferation. Cell‐cycle impairment accounted for altered cytoskeletal organization, endoproliferation and apoptosis, whereas a compensatory mechanism sustained the increased cyclinD1 transcript levels. Sox9, Agg and TGFs were overexpressed, but not Col2. IL transcripts were massively downregulated. These events were dose‐related and transient. Overall, in spite of a higher Rev‐induced transcriptional activity for extracellular matrix components and in spite of a Rev‐treated cell phenotype closer to that of the three‐dimensional native articular chondrocyte, Rev effects seem unleashed from a full regained chondrogenic potential.